Clinical validation of the Psychotic Depression Assessment Scale (PDAS) against independent global severity ratings in older adults. Issue 4 (4th March 2018) - Vermeulen, Tom; Lemey, Lieve; Van Diermen, Linda; Schrijvers, Didier; Madani, Yamina; Sabbe, Bernard; Van Den Bossche, Maarten J.A.; van der Mast, Roos C.; Østergaard, Søren D.
Abstract: Objectives: According to a recent study, ratings on the Psychotic Depression Assessment Scale (PDAS) obtained via a dedicated semi-structured interview are valid measures of the severity of psychotic depression. This study aimed to further test the validity, scalability and responsiveness of the PDAS in older adults using independent ratings on the Clinical Global Impression Scale – Severity (CGI-S) and the Montgomery-Asberg Depression Rating Scale (MADRS) as references. Methods: Ratings were performed at admission and discharge at two old age psychiatric wards in Flanders, Belgium. In total, 62 older adults (mean age: 74.3 years) with psychotic depression were included. The PDAS was rated by trained nurses using the semi-structured PDAS interview. Senior psychiatrists scored the participants on the CGI-S. Psychologists or experienced nurses rated participants on the MADRS. Clinical validity was assessed by correlating the PDAS total scores with CGI-S ratings and MADRS total scores. Mokken analysis was performed to assess the scalability of the PDAS. Responsiveness was assessed by comparing the proportion of participants in remission (PDAS total score <8 at study baseline and endpoint). Results: The Spearman correlation coefficients were 0.76 and 0.79 for the PDAS versus CGI-S and PDAS versus MADRS, respectively. The Mokken analysis yielded a Loevinger coefficient of 0.46, which is indicative of scalability. At admission, no participants met the PDAS remission criterion. At discharge, 54% (95% confidence interval: 47%–60%) of the patients met this criterion. Conclusion: The PDAS appears to be a clinically valid, scalable and responsive measure of the severity of psychotic depression in older adults.